Low-grade endotoxaemia enhances artery thrombus growth via Toll-like receptor 4: implication for myocardial infarction. (3rd January 2020) - Carnevale, Roberto; Sciarretta, Sebastiano; Valenti, Valentina; di Nonno, Flavio; Calvieri, Camilla; Nocella, Cristina; Frati, Giacomo; Forte, Maurizio; d'Amati, Giulia; Pignataro, Maria G; Severino, Anna; Cangemi, Roberto; et al.
Abstract: Aims: Low-grade endotoxaemia is detectable in human circulation but its role in thrombosis is still unclear. Methods and results: We measured serum lipopolysaccharide (LPS) concentration, soluble P-selectin (sP-selectin), a marker of platelet activation, and zonulin, a marker of gut permeability, in peripheral circulation, coronary thrombi, and intracoronary blood of patients with ST-elevation myocardial infarction (STEMI, n  = 50) and stable angina (SA) ( n  = 50), respectively, and in controls ( n  = 50). Experimental study was carried out in mice to assess if Escherichia coli -LPS ( E. coli -LPS) possess thrombotic property. Coronary thrombi from STEMI showed higher concentrations of LPS, sP-selectin vs. intracoronary blood of SA and peripheral blood of controls ( P  < 0.001). Zonulin was higher in STEMI compared to the other two groups [4.57 (3.34–5.22); 2.56 (0.41–4.36); 1.95 (1.22–2.65) ng/mL; P  < 0.001] and correlated with LPS (Rs = 0.585; P  < 0.001). Escherichia coli DNA was positive in 34% of STEMI vs. 12% of SA and 4% of controls ( P  < 0.001). In a subgroup of 12 STEMI, immunohistochemical analysis of coronary thrombi showed positivity for leucocyte Toll-like receptor 4 (TLR4), cathepsin G, and LPS from E. coli in 100%, 80%, and 25% of samples, respectively. E. coli -LPS injected in mice to reach LPS concentrations like those detected in coronary thrombi was associated with enhanced artery thrombosis and platelet activation, an effect blunted by TLR4 inhibitor co-administration. In vitro study demonstrated that LPS from E. coli enhanced platelet aggregation via TLR4-mediated leucocyte cathepsin G activation. Conclusion: ST-elevation myocardial infarction patients disclose an enhanced gut permeability that results in LPS translocation in human circulation and eventually thrombus growth at site of artery lesion via leucocyte–platelet interaction.